2017
DOI: 10.1038/pcan.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle guidelines for managing adverse effects on bone health and body composition in men treated with androgen deprivation therapy for prostate cancer: an update

Abstract: Background:Men treated with androgen deprivation therapy (ADT) for prostate cancer are prone to multiple treatment-induced adverse effects, particularly with regard to a deterioration in bone health and altered body composition including decreased lean tissue mass and increased fat mass. These alterations may partially explain the marked increased risk in osteoporosis, falls, fracture and cardiometabolic risk that has been observed in this population.Methods:A review was conducted that assessed standard clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 100 publications
(162 reference statements)
5
70
0
2
Order By: Relevance
“…Previous research has indicated that duration of ADT appears to be important when considering lean mass, with losses of up to 2.6-3.2% of total body lean mass occurring within the initial 6-9 months of treatment [195] . Given that around one-third of men in our study had not received ADT for this duration when assessed for this study, it is possible that we may have underestimated the true effects of chronic ADT (≥ six months) on total body and regional lean mass.…”
Section: Effects Of Androgen Deprivation Therapy On Total Body and Rementioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has indicated that duration of ADT appears to be important when considering lean mass, with losses of up to 2.6-3.2% of total body lean mass occurring within the initial 6-9 months of treatment [195] . Given that around one-third of men in our study had not received ADT for this duration when assessed for this study, it is possible that we may have underestimated the true effects of chronic ADT (≥ six months) on total body and regional lean mass.…”
Section: Effects Of Androgen Deprivation Therapy On Total Body and Rementioning
confidence: 99%
“…Notably, the rationale for calcium supplementation, and in part vitamin D, predominantly stems from the need to address decreases in areal and volumetric BMD in men treated with ADT [195] , and is beyond the scope of this thesis. The following sections will focus on the safety and potential efficacy of supplementation with vitamin D, calcium and protein in ADT-treated men.…”
Section: The Role Of Nutritional Supplementation On Muscle Fat and Pmentioning
confidence: 99%
See 3 more Smart Citations